CHALLENGES AND RISKS ASSOCIATED WITH PHARMACEUTICAL SUPPLY CHAIN. A SYSTEMATIC REVIEW. - Saeed Kheder Alzahrani, Mohammed Musaed Alharbi, Mohammed Mesfer Alghamdi, Abdullah Hammad Alsuwat, Ali Hamed Alzobaydi, Khalil Abdullah Alzahrani, Sulaiman Raja Alallasi, Mahdi Awad Alamri, Osama Owaidah Aljehani, Saeed Abdullah Alghamdy,; Basem Magbool Albeladi, (Chelonian Research Foundation, 2022)
The pharmaceutical supply chain poses risks and challenges to both providers and consumers. But in the context of a health-conscious society, managing pharmaceutical supply chains presents several complexities because it involves many key components and stakeholders to efficiently deliver life-saving medicines that are vital to patients. In such a complex process, the stakes are high for pharmaceutical companies. Incorrectly distributed drugs can harm their reputation, customer satisfaction, and potential profits. The purpose of this review is to break down the fundamentals of the pharmaceutical supply chain to uncover strategies for overcoming the most common challenges and ways to get patients, consistent access to current and new drugs. Bibliographic databases such as PubMed, Scopus, Web of Science and scientific search engines such as Google scholar, were searched for pharmaceutical supply chain risk management studies carried out until January 2022. Keywords- Supply chain, pharmacy, challenges, PBM